Acquisition and pricing strategies in hybrid manufacturing-remanufacturing systems. (October 2020) - Li, Kai; Liu, Jing; Fu, Hong; Liu, Bohai
Highlights: We considered Hybrid manufacturing and remanufacturing systems in a closed-loop supply chain. A grading acquisition mode is adopted in the remanufacturing system. The acquisition and pricing strategies of different remanufacturers are studied. The impact of acquisition timing on profit and environment for a remanufacturer is discussed. Abstract: There are two typical cases of acquisition and remanufacturing in a closed-loop supply chain: The third party remanufacturer (3PR) and the original equipment manufacturer (OEM) separately acquire and remanufacture used products. The used products have different qualities, and they can be classified for acquisition in reality. In this paper, under the grading acquisition mode, we compare the acquisition strategies of used products and the pricing strategies of new products and remanufactured products in different manufacturing-remanufacturing systems. Then we further study the impact of the timing of remanufacturing on the profit and the environment. From an environmental perspective, the 3PR is willing to acquire and remanufacture used products at the best grade, whereas the OEM may choose more grades. The latter can reduce environmental impact. From an economic perspective, as long as the total cost of acquiring and remanufacturing used products does not exceed the threshold, remanufacturing can bring more profit for the OEM than only selling new products. Moreover, when consumers' preference for remanufactured products is relatively high, and the total cost of acquisition and remanufacturing does not exceed the threshold, the OEM can engage in remanufacturing business before the new products exit from the market.